Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 1 - Test - Page 111: 13



Work Step by Step

First, simplify within the parentheses by distributing 3 to obtain: $=6-2[3x+3-5] \\=6-2[3x-2]$ Distribute $-2$ to obtain: $=6-6x-(-4) \\=6-6x+4$ Simplify by combining like terms: $\\=-6x+(6+4) \\=-6x+10$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.